Yacon powder mix: Effects of the composition and the process of microencapsulation by spray drying - María Isabel Arango-Torres; Misael Cortés-Rodríguez; Esteban Largo-Ávila; Manuela Gallón-Bedoya; Rodrigo Ortega-Toro (Heliyon, 2024)
Yacon is a tuber known as a healthy food due to its effects as an antidiabetic, anti-inflammatory, anticancer, and prebiotic agent; it is rich in fructooligosaccharides (FOS) and antioxidants, and due to its sweet taste and low-calorie content, it is used as a substitute for ordinary sugar. This research aimed to evaluate the influence of the composition of the feed and the microencapsulation process by spray drying (SD) on the properties of a yacon powder mixture (YP). Response surface methodology with a central composite design with a face-centered composition (α = 1) was used, considering the independent variables: inulin (IN) (3–5% w/w), maltodextrin (MD) (3–5% w/w), air inlet temperature (AIT) (140–160 °C), air outlet temperature (AOT) (75–85 °C) and atomizer disc speed (ADS) (18000–22000 rpm), and the dependent variables: moisture (Xw), water activity (aw), hygroscopicity (Hy), solubility (S), particle size (percentile D10, D50, and D90), total phenols (TP), antioxidant capacity (ABTS and DPPH), color (CIE-Lab*) and yield (Yi). The suspension formulation contained xanthan gum (0.167 %) and a mixture of ascorbic and citric acids (0.3 %). The aw and Xw values of the YP guarantee its microbiological stability; however, the process formulation produces a complex matrix (FOS- sugars- MD - IN) with high affinity for water, which favors adsorption phenomena (hygroscopic material) and high reconstitution (high solubility). The independent variables that best fit the experimental optimization criteria were: IN = 3.0 %, MD = 5.0 %, AIT = 143.7 °C, AOT = 80.1 °C, ADS = 22000 rpm, where Yi = 84.2 %, and the quality of the YP: Xw = 2.4 %, aw = 0.220, Hy = 23.0 %, S = 96.9 %, D10 = 10.6 μm, D50 = 23.4 μm and D90 = 169.3 μm, TP = 1228.2 mg gallic acid equivalent/100 g, ABTS = 2295.9 mg Trolox equivalent (TE)/100 g, DPPH = 5192.3 mg TE/100 g, L* = 80.5, a* = 5.1 and b* = 17.4. SD is an effective technology that positively impacts the development of new food products. In addition, the YP could have multipurpose applications for the industry, generating value in this agri-chain.